Theory and Application of Gob-Side Entry Retaining in Thick Three-Soft Coal Seam. (2nd July 2021) - Shen, Junchao; Zhang, Ying
Abstract : With the characteristic of less roadway excavation and high resource recovery, gob-side entry retaining (GER) technology is a safe and efficient green mining technology. Many experts and scholars have done extensive research on its principle and application. However, GERs are rarely used in thick soft coal seams. In this paper, based on the geological conditions of a coal mine in China, we propose a novelty approach of GER in thick three-soft coal seam (it means a single seam with a soft roof and a soft floor). The engineering scheme includes roadway expansion, large section roadway support, cutting roof to relieve pressure, and road-inside backfill body construction. The established mechanical and numerical calculation models effectively guide the engineering practice. Field observations showed that all the processes met the requirements of field production. The research results could provide theoretical guidance for the application of GER under similar geological conditions.